2022
DOI: 10.1038/s41416-022-01844-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic routes and time intervals for ovarian cancer in nine international jurisdictions; findings from the International Cancer Benchmarking Partnership (ICBP)

Abstract: Background International Cancer Benchmarking Partnership Module 4 reports the first international comparison of ovarian cancer (OC) diagnosis routes and intervals (symptom onset to treatment start), which may inform previously reported variations in survival and stage. Methods Data were collated from 1110 newly diagnosed OC patients aged >40 surveyed between 2013 and 2015 across five countries (51–272 per jurisdiction), their primary-care physicians (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The diagnostic pathway and routes to diagnosis of cancer patients with lung, colorectal and ovarian cancer have also been described in bespoke samples of patients in several jurisdictions. [27][28][29] Implications for research and practice…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The diagnostic pathway and routes to diagnosis of cancer patients with lung, colorectal and ovarian cancer have also been described in bespoke samples of patients in several jurisdictions. [27][28][29] Implications for research and practice…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…A large survey of North American women with ovarian cancer found that 64% believed there were health system barriers to a prompt diagnosis [13], including referral to gastroenterologists, a lack of further investigations, and misattribution or non-recognition of symptoms [14]. Given that disease stage at diagnosis is a critical prognostic factor [15], prompt and efficient diagnosis are a critical issue warranting further inquiry [16]. There is some evidence of poor alignment between patients' recall and medical records regarding time to ovarian cancer diagnosis [17], which suggests investigations using medical records are needed to obtain a comprehensive picture of pathways to ovarian cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%